1994
DOI: 10.1007/bf00190591
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal development of neuropeptide Y- and calcitonin gene-related peptide-immunoreactive nerves in the rat urinary bladder

Abstract: The postnatal development of neuropeptide Y- and calcitonin gene-related peptide-immunoreactive (NPY-IR and CGRP-IR) nerve fibers in the rat urinary bladder was investigated using whole-mount preparations and cryostat sections. In newborn and 3-day-old rats, many NPY-IR nerve fibers were observed in the subserous and muscle layers. Many NPY-IR nerve cell bodies clustered at branching points of the subserous nerve bundles. Within 4 weeks after birth, these cell bodies drastically decreased in number and spread … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
19
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 32 publications
(43 reference statements)
3
19
1
Order By: Relevance
“…This reorganization leads to downregulation of primitive spinal mechanisms and upregulation of mature supraspinal pathways (12, 13). Previous studies have suggested the importance of neuroactive compounds in the process of maturation of the micturition reflexes during prenatal and early postnatal development (19,26,41).There is a substantial body of literature that supports a functional role for ATP in the modality of mechanotransduction in the urinary bladder (7, 57). ATP can be produced and released from the urothelium in response to stretch (21,45,46), and this release can be augmented in urothelial cells from patients with interstitial cystitis (IC) (45) and benign prostatic hyperplasia (46).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This reorganization leads to downregulation of primitive spinal mechanisms and upregulation of mature supraspinal pathways (12, 13). Previous studies have suggested the importance of neuroactive compounds in the process of maturation of the micturition reflexes during prenatal and early postnatal development (19,26,41).There is a substantial body of literature that supports a functional role for ATP in the modality of mechanotransduction in the urinary bladder (7, 57). ATP can be produced and released from the urothelium in response to stretch (21,45,46), and this release can be augmented in urothelial cells from patients with interstitial cystitis (IC) (45) and benign prostatic hyperplasia (46).…”
mentioning
confidence: 99%
“…This reorganization leads to downregulation of primitive spinal mechanisms and upregulation of mature supraspinal pathways (12, 13). Previous studies have suggested the importance of neuroactive compounds in the process of maturation of the micturition reflexes during prenatal and early postnatal development (19,26,41).…”
mentioning
confidence: 99%
“…For whole-mount staining, embryos were incubated in 100% dimethyl sulfoxide for 3 hours at room temperature [Iuchi et al, 1994]. They were pretreated with 3% normal bovine serum for 2 hours at room temperature.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Pharmacologically the responses to KCl, 6,7 Carbachol (CA), 7 ATP, 6,7 and Substance P 6 were significantly increased in neonatal bladders from different species. Further reports have been made on age-dependent evolutions in endothelin receptors, 8 neuropeptide Y-and CGRP-related immunoreactive nerve fibres, 9 purinoreceptor expression 10 and calcium-handling in excitation-contraction coupling. 11 (For reviews on age-dependent evolutions in autonomic bladder function, see Refs.…”
Section: Introductionmentioning
confidence: 96%